Interpretation of Hadith on Online Transactions in Sharia Economics: A Study of the Prohibition of Gharar in the Digital Era - Rifai, Ahmad (Zona Law And Public Administration Indonesia, 2024)
This study aims to analyze the implementation of online transactions in the sharia economy by focusing on the interpretation of hadith about the prohibition of gharar in the digital era. Gharar, which is uncertainty in a transaction, can pose risks and losses to the parties involved. The method used in this study is a literature study with a qualitative approach, which includes analysis of relevant hadiths, literature review on sharia e-commerce, and interviews with business people in this sector. The data collected includes explanations of gharar in the context of buying and selling, challenges in online transactions, and efforts by business people to minimize gharar through more transparent practices. The results show that although many sharia-based e-commerce platforms have implemented measures to reduce uncertainty, there are still gaps that need to be addressed, such as increasing awareness among businesses and consumers regarding sharia principles. The conclusion of this study emphasizes the importance of applying the values contained in the hadith about the prohibition of gharar to create online transactions that are fairer, more transparent, and in accordance with the principles of sharia economics, so that it can encourage the sustainable growth of the sharia e-commerce sector